"Economic Memories" of the Aftermath of the 1989 Revolutions in East Germany and the Czech Republic. Issue 1 (February 2021) - Hilmar, Till
How does the aftermath of 1989 shape the meaning of this event today? On the basis of an interview study with sixty-seven respondents from former East Germany and the Czech Republic administered in 2016–2017, this article asks how individuals articulate "economic memories" against the background of the 1990s, a time in which the transition to democracy was accompanied by labor market ruptures. It documents how salient themes of change are narrated in terms of work and its moral dimensions; and how memories of the time are concerned with mobilizing one's skills in the face of economic change. The article distinguishes five accounts by which respondents differently incorporate the historical event of 1989 into a vernacular, biographical logic. This framework offers a "bottom-up" perspective as a contribution to our understanding of the ongoing contestations over the meaning of the 1989 revolutions.